The allocation of resources : theory and policy - George, Kenneth Desmond; Shorey, John. (London : Boston : Allen & Unwin, 1978)
The text covers the following topics: Optimal allocation and economic welfare -- Changes in welfare -- The distribution of income and wealth -- Public utility pricing and investment -- Factor indivisibilities, size and efficiency in the private sector -- Problems of adjustment -- Externalities and public goods -- Cost-benefit analysis.
Includes bibliographical references: p. [265]-269 and index.
rpm 18/10/2017
Loans
Keywords: Microeconomics